2020
DOI: 10.1016/j.cegh.2020.04.019
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology and phylogenetic analysis of respiratory viruses from 2012 to 2015 – A sentinel surveillance report from union territory of Puducherry, India

Abstract: Background: Acute respiratory infections (ARI) are the most common illnesses affecting people of all ages worldwide. Viruses contribute to 30-70% of acute respiratory infections. Identification of these respiratory viruses is not given high priority except influenza; however, the knowledge about prevalence of non-influenza viruses, their seasonal pattern and genetic evolution have significant epidemiological value. Methods: As a part of National Influenza-like illness surveillance programme, respiratory specim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 47 publications
0
3
0
Order By: Relevance
“…The South India region with 2,298 cases reported 1,013 positive detections for respiratory virus, and around 50% of the cases detected were RSV, which is higher than that in any other region in the country (Akila, 2019;Kini et al, 2019;Abinaya et al, 2020;Anand and Nimmala, 2020;Hindupur et al, 2020;Palani and Sistla, 2020).…”
Section: South Indiamentioning
confidence: 87%
“…The South India region with 2,298 cases reported 1,013 positive detections for respiratory virus, and around 50% of the cases detected were RSV, which is higher than that in any other region in the country (Akila, 2019;Kini et al, 2019;Abinaya et al, 2020;Anand and Nimmala, 2020;Hindupur et al, 2020;Palani and Sistla, 2020).…”
Section: South Indiamentioning
confidence: 87%
“…Among those positive for CoVs, type 229E was the most prevalent type (n = 6, 75.0%), followed by HKU1 (2, 25%) contrary to most reports where OC43 is usually the most common [ 44 , 45 ]. Despite being a known causative for URTIs, few studies investigated the epidemiological traits of parechovirus [ 46 ].…”
Section: Discussionmentioning
confidence: 72%
“…Again, it was found that the cases with HCoVs were very low. 13 A meta-analysis on the burden of respiratory viruses and diseases in different states of India was conducted using data from 1970 to 2020 and this study revealed that India has higher rates of infections of respiratory syncytial virus, influenza, parainfluenza and a trend of higher rate of rhinovirus infections. 14 But infection due to HCoVs was hardly reported from India.…”
mentioning
confidence: 99%